Hadron masses in a chirally symmetric confining model - Bicudo, P. J.A.; Krein, G. [UNESP]; Ribeiro, J. E.F.T.; Villate, J. E. (American Physical Society (APS), 1992)
Hadron masses are investigated in the framework of a chirally invariant, effective quark Hamiltonian. The hyperfine, spin-orbit, and tensor forces are found to be connected to the chiral angle, which measures the extent of vacuum condensation. The only finite eigenvalues of this Hamiltonian are shown to be color singlets. The chiral angle is obtained as a solution of the associated mass-gap equation. With the same bare parameters used when studying mesons with light quarks, we are able to account for the spectroscopy of charmonium and the N- mass difference. The results are reasonably good. © 1992 The American Physical Society.